Ultrasound Assisted One-pot Synthesis of Dihydropyrimidinones Using Holmium Chloride As Catalyst - S. Kakaei; H. Sid Kalal; H. Hoveidi (Journal of Sciences, Islamic Republic of Iran)
A simple and green chemical procedure was reported for the synthesis of dihydropyrimidinones from various aldehydes, ethyl acetoacetate and urea or thiourea using  holmium chloride as catalyst. The reactions were performed under solvent free conditions with ultrasound irradiation as the energy source. The advantages of this protocol include the excellent yield, operational simplicity, short time and the avoidance of the use of organic solvents and friendly preparation. Products were identified by mp. and IR, NMR and Mass spectroscopies.